Koroner arter bypass greftleme cerrahisi sonrası atriyal fibrilasyonu gelişen hastaların yakın dönem takiplerinde atrial fibrilasyonun prognozu ve mortalite üzerinde etkisinin araştırılması Prognosis and mortality effects of atrial fibrillation in short-term follow-up of patients developing atrial fibrillation after coronary artery bypass grafting surgery - MASRİOĞLU, AHMET (My University, 2025)
AMAÇ: Koroner Arter Bypass Greftleme (CABG) cerrahisi sonrası atriyal fibrilasyonu (AF) gelişen hastaların yakın dönem takiplerinde AF'nin prognozu ve mortalite üzerindeki etkilerini incelemektir , CABG sonrası AF'nin hastaların klinik özellikleri ile ilişkisi ve postoperatif dönemdeki sonuçlarla arasındaki bağlantılar değerlendirilecektir. Bu bağlamda, AF'nin hastaların genel sağkalım oranları, komplikasyon sıklığı ve yaşam kalitesi üzerindeki etkileri araştırılacak ; bu durumun, CABG cerrahi müdahalesi sonrası AF gelişen hastaların iyileşme süreçleri üzerindeki olumsuz yükü açığa çıkaracaktır . GEREÇ VE YÖNTEM: 2019 Ocak – 2024 Haziran tarihleri arasında Bezmialem Vakıf Üniversitesi hastanesinde Kalp Ve Damar Cerrahi Kliniğinde izole Koroner Arter Bypass Grefleme (CABG ) operasyonu geçiren hastaları (N = 449 ) , Postoperatif dönemde AF tanısı almış hasta grubu ( N =118 ) ve AF olmayan kontrol hasta grubu (N = 331) olarak iki gruba ayırarak AF gelişen hasta grubun postoperatif ilk 6 aylık takip dönemde gelişen komplikasyonları ve mortaliteyi inceleyerek AF ile ilişkisi analiz edildi .
OBJECTIVE : The aim of this study is to evaluate the prognosis of atrial fibrillation (AF) and its impact on mortality and morbidity in the short-term follow-up of patients who present AF after coronary artery bypass grafting (CABG) surgery. The relationship between AF and the clinical characteristics of patients, as well as its association with postoperative outcomes, will also be evaluated. Additionally, the effects of AF on overall survival rates, complication frequency, and quality of life will be investigated. These results aim to guide clinicians in improving the management and recovery process of this patient population following CABG surgical intervention . MATERIALS AND METHODS : Between January 2019 and June 2024, a total of 449 patients who underwent isolated coronary artery bypass grafting (CABG) surgery in the Department of Cardiovascular Surgery at Bezmialem Vakif University Hospital were included in this study. The patients were divided into two groups: the postoperative atrial fibrillation (AF) group (N = 118) and the non-AF control group (N = 331). Postoperative mortality and morbidity during the first 6 months of follow-up were analyzed in the AF group, and their association with AF was evaluated.
Keywords: Göğüs Kalp ve Damar Cerrahisi = Thoracic and Cardiovascular Surgery